Online attachment in tax enforcement and the crime of abuse of authority (art. 36 of Law No. 13,869/2019) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
Online garnishment is a fast-foward effectiveness tool on tax enforcement. The new law of Abuse of authority criminalized the non-release of excess of blocked amounts. The new penal act is ought to be unconstitutional.
Keywords: Tax enforcement; online attachment; SISBAJUD; unavailability of financial assets; crime; article 36 of Law 13.869/2016